Perancangan Sistem Informasi Manajemen Pengelolaan Aset Berbasis Web pada PT Global Asia Sinergi - Ari Yanto; Ari Hidayatullah (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
Manual asset management often causes problems such as data duplication, recording errors, and difficulties in tracking asset status. This study aims to design and develop an efficient, adaptive, and user-friendly web-based Asset Management Information System using the Agile (Scrum) development method and measuring its success through the System Usability Scale (SUS) evaluation. The study was conducted at PT Global Asia Sinergi with direct users as active participants in each development iteration. The development process was carried out through several sprints covering the planning, implementation, testing, and evaluation stages with users. The Agile evaluation results showed an average sprint success rate of 88%, with a stable velocity of 45 story points per iteration and positive user feedback (a score of 4.3 out of 5). Meanwhile, the SUS test results obtained an average score of 78.5, which falls into the “Good Usability” category, indicating that the system is easy to use, consistent, and reliable in supporting the company's operational activities. Thus, it can be concluded that the application of the Agile method in the development of an asset management information system can improve the efficiency of the development process while producing a system with a high level of usability in accordance with user needs.